Factors affecting the hospitalization of female patients with asthma - Perincek, Gökhan; Avcı, Sema (Journal of Surgery and Medicine, 2019)
Aim: Asthma is one of the most common chronic respiratory diseases and an important public health problem leading to mortality. The aim of this study was to evaluate the hospitalization rates of female patients with asthma. Methods: This cross-sectional study was conducted with the approval of a university hospital ethics committee between September 2018 and January 2019. The study included a total of 183 females: 56 patients with exacerbation were included in Group 1 and 127 patients with stable asthma constituted Group 2. Demographic data, pulmonary function test results, number of hospital admissions, hospitalization rates and laboratory findings were evaluated. All statistical calculations were performed with SPSS 23.0 for Windows. Results: The mean age, number of hospitalizations and admissions to the emergency room were significantly higher in Group 1 (P=0.003, P<0.001 and P<0.001, respectively). Patients in Group 1 had lower oxygen saturations, FEV1, FVC, FEV1/FVC values, higher respiratory and heart rates, blood glucose, lactate dehydrogenase, c-reactive protein, lactate, phosphorus, high-density lipoprotein, calcium levels, white blood cell and neutrophil counts. Increased eosinophil count and decreased basophil count were associated with increased emergency room admission rates (P=0.043). Conclusion: Women admitted to the hospital with asthma exacerbation were older and had an increased number of hospitalization rates. Higher eosinophil blood levels were associated with recurrent hospital admissions.